Heavy metals in edible seafood - Emelia, Giri (Universiti Malaysia Sarawak, UNIMAS, 2009)
Commercial fish and shellfish obtained from the Satok market in Kuching was analyzed for selected heavy metals content (Pb, Cr, Co, Ni, Mg, Fe, Zn, Cu and Mn). The samples were evaluated using Flame Atomic Absorption Spectrometer (FAAS). The concentration of Pb, Cr, Cr, Co, Ni, Mg, Fe, Zn, Cu and Mn ranges from 0.5-1.7 mg/kg, 12.0-17.7 mg/kg, 0.7-3.7 mg/kg, 9.0-26.7 mg/kg, 227.0-636.5 mg/kg, 59.3-141.4mg/kg, 19.0-50.0 mg/kg, 2.7-8.7 mg/kg, and 17.7-32.7 mg/kg respectively. The results obtained show that fish and shellfish samples obtained from the market are safe for human consumption as the levels of heavy metals among all the edible seafood samples not exceeding the maximum permissible limits which are stipulated under Joint Food and Agriculture Organization/World Health Organization Expert Committee on Food Additives (JECFA) and Malaysian Food Act 1996 guidelines. Statistical analysis of One-Way ANOVA showed significantly difference (P < 0.05) between heavy metals contents in all the samples analyzed.